Harry Potter and the sorcerer's stone - Rowling, J.K. (New York : Scholastic, 1999)
Juvenile fiction.
Keywords: Fantasy fiction -- Juvenile; Hogwarts school of witchcraft and wizardry (Imaginary place) -- Juvenile fiction; Magic -- Juvenile fiction; Schools -- Juvenile fiction